Yo o las trampas de la biografía. - Mackenbach, Werner (2012)
This essay proposes a new lecture of Yolanda Oreamuno's work that may overcome its canonization based on "biographist" and "contentist" approaches and the supposed identity of work and life, which have dominated in the critic up to the moment. One possible lecture which meets these requisites -and which is being realized in this article- could be one of his novel La ruta de su evasión from the perspective of literary geography, that means, a lecture which in contrast to Manuel Picado Gómez's classification of the text as a novel of personage and not a novel of space, analyzes the space of and in this novel in four dimensions: the representation of physical spaces, the signifying of physical spaces, the text as space and the literary space between the author, the work and the readers.